On the Balance between Magnetization and Coercivity of MnBi Green Powders and Magnets Prepared Thereof - Nguyen Xuan, Truong; Vu, Ky Hong; Nguyen, Vuong Van (VNU Journal of Science: Mathematics - Physics, 2021)
Currently, MnBi magnetic material is promising to be very potential for low-cost high-temperature permanent magnetic applications. The most attractive parameters are the high magnetocrystalline anisotropy energy and its positive thermal coefficient which allow a high coercivity of MnBi magnets working even at 150 – 200 o C. This advantage is paid by the moderate value of magnetization, so the high energy product of MnBi magnets depends on how one can keep a good balance between the remanent magnetization M r and the coercivity b H c . The paper considers this problem and discusses how to regulate the processing route to keep this balance to enhance the performance of MnBi green powders and MnBi bulk magnets prepared thereof